"And we just have to keep going": Task shifting and the production of burnout among overdose response workers with lived experience. (February 2021) - Olding, Michelle; Boyd, Jade; Kerr, Thomas; McNeil, Ryan
Abstract: Overdose response programs in North America increasingly employ task shifting—shifting overdose response tasks to less specialized workers—to increase effectiveness and promote involvement of people with lived/living experience of drug use (PWLE). In Canada, task shifting has occurred through community-driven implementation of overdose response programs staffed primarily by PWLE. The implications of this task shifting on workers' well-being and service delivery has received little scholarly consideration, despite reports of widespread burnout among frontline responders. This study examines experiences and drivers of burnout among PWLE working at low-barrier supervised consumption sites ("Overdose Prevention Sites" or OPSs) in Vancouver, Canada. Between December 2016 and March 2020, we conducted ethnographic fieldwork at four OPSs, including in-depth interviews with 23 overdose response workers, three site-based focus groups with 20 additional workers, and 150 h of naturalistic observation. Data were analyzed to explore how working conditions, labour arrangements, economic insecurity and social disadvantage shaped burnout. We found that overdose response workers commonly reported burnout, which they attributed to the precarious and demanding nature of their work. While casual positions offered low-barrier employment, PWLE often lacked the wages and benefits enjoyed by other frontline workers, with limited supports and opportunities for advancement. Due to their social position within drug-using networks, PWLE's work encompassed hidden care work that participants felt was constant and undervalued. The scarcity of permanent full-time positions, alongside barriers to transitioning into formal employment, prevented many PWLE from earning livable wages or taking time off to 'recharge.' This study highlights how the devaluing and casualization of overdose response labour, compounded by other dimensions of structural vulnerability, are central to burnout among overdose response workers with lived experience. Interventions to address burnout within this setting must extend beyond individual-level interventions (e.g. counselling, self-care) to also strengthen working conditions and economic security of PWLE. Highlights: Rapid ethnography of low-barrier supervised consumption sites in Vancouver, Canada. Examines burnout among overdose responders with lived experience of drug use. Describes social and structural contributors to burnout. Highlights need to strengthen working conditions, job protections and supports.